Clinical and neurocognitive profiles of a combined clinical high risk for psychosis and clinical control sample: latent class analysis - Stüble, Miriam; Schultze-Lutter, Frauke; Kaess, Michael; Franscini, Maurizia; Traber-Walker, Nina; Walger, Petra; Schimmelmann, Benno G.; Vogeley, Kai; Kambeitz, Joseph; Kindler, Jochen; Michel, Chantal (BJPsych Open, 2024)
BackgroundThe clinical high-risk (CHR) state for psychosis demonstrates considerable clinical heterogeneity, presenting challenges for clinicians and researchers alike. Basic symptoms, to date, have largely been ignored in explorations of clinical profiles.AimsWe examined clinical profiles by using a broader spectrum of CHR symptoms, including not only (attenuated) psychotic, but also basic symptoms.MethodPatients (N = 875) of specialised early intervention centres for psychosis in Germany and Switzerland were assessed with the Schizophrenia Proneness Instruments and the Structured Interview for Psychosis-Risk Syndromes. Latent class analysis was applied to CHR symptoms to identify clinical profiles. Additionally, demographics, other symptoms, current non-psychotic DSM-IV axis I disorders and neurocognitive variables were assessed to further describe and compare the profiles.ResultsA three-class model was best fitting the data, whereby basic symptoms best differentiated between the profiles (η2 = 0.08-0.52). Class 1 had a low probability of CHR symptoms, the highest functioning and lowest other psychopathology, neurocognitive deficits and transition-to-psychosis rate. Class 2 had the highest probability of basic and (attenuated) positive symptoms (excluding hallucinations), lowest functioning, highest symptom load, most neurocognitive deficits and highest transition rate (55.1%). Class 3 was mostly characterised by attenuated hallucination, and was otherwise intermediate between the other two classes. Comorbidity rates were comparable across classes, with some class differences in diagnostic categories.ConclusionsOur profiles based on basic and (attenuated) psychotic symptoms provide clinically useful entities by parsing out heterogeneity in clinical presentation. In future, they could guide class-specific intervention.